Solid-liquid separation garbage can - QU JIANGXUE (2013)
The utility model relates to a garbage can, in particular to a solid-liquid separation garbage can. The solid-liquid separation garbage can comprises an outer shell with an inner cavity, a cover body, a filter screen plate, a drain tank and a blow-off pipe. The filter screen plate is arranged in the inner cavity of the outer shell in an inclining mode and divides the inner cavity of the outer shell into an upper solid waste containing cavity and a lower liquid waste containing cavity, the drain tank is arranged on the bottom portion of the outer shell and is in detachable and sliding connection with the outer shell, the bottom face of the containing cavity of the drain tank is an inclined face, the blow-off pipe is communicated with the containing cavity of the drain tank, a drain outlet is formed in the side face of the outer shell, the cover body is rotatably connected to the drain outlet, and the dirt inlet of the blow-off pipe is connected with the lowest point of the containing cavity of the drain tank.